2009
DOI: 10.1001/archinternmed.2009.102
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Errors and Outcomes Related to Inconsistent Information Transmitted Through Computerized Order Entry

Abstract: Background Although several types of computerized provider order entry (CPOE)-related errors may occur, errors related to inconsistent information within the same prescription (ie, mismatch between the structured template and the associated free-text field) have not been described, to our knowledge. We determined the nature and frequency of such errors and identified their potential predictive variables. Methods In this prospective study, we enrolled pharmacists to report prescriptions containing inconsisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 27 publications
(40 reference statements)
1
48
0
1
Order By: Relevance
“…Competence builds on a foundation of basic skills, and knowledge [41]. Inadequate knowledge of the health IT mechanism or less familiar with the systems was common reason associated with errors [13,[42][43][44]. Lack of knowledge about health IT was the frequent reason for healthcare practitioners to use paper in conjunction with health IT.…”
Section: Personmentioning
confidence: 99%
See 1 more Smart Citation
“…Competence builds on a foundation of basic skills, and knowledge [41]. Inadequate knowledge of the health IT mechanism or less familiar with the systems was common reason associated with errors [13,[42][43][44]. Lack of knowledge about health IT was the frequent reason for healthcare practitioners to use paper in conjunction with health IT.…”
Section: Personmentioning
confidence: 99%
“…Besides, the healthcare practitioners used their own way in completing tasks rather than to use the functions available in the systems [43]. Singh et al [42] discovered that inadequate knowledge of the prescription ordering mechanism was a common reason for the pharmacists to use free-text comment in 88.9% of cases rather than to use the structured template to fill the prescription. The used of free-text comment were often associated with errors in which 20.1% of the prescription errors resulted in considerable, very serious, serious permanent damage, or death.…”
Section: Personmentioning
confidence: 99%
“…Computerized physician order entry (CPOE) systems, which allow health care providers to send patients' prescription orders, can help in preventing prescription errors and patient harm (Radley et al 2013). Singh et al (2009) reported approximately 1 % of 56,000 CPOE prescriptions contained errors. Radley et al's (2013) study showed a 12.5 % reduction of medical errors through the use of a CPOE system.…”
Section: Organizational Systemsmentioning
confidence: 99%
“…The software used by prescribers should also be updated regularly to reflect the currently funded brand. • Whilst computer generated prescriptions may reduce some types of errors (such as legal requirements), they may introduce new errors [10] such as incorrect dose and dosage form selection and prescribers still need to exercise due care.…”
Section: Recommendationsmentioning
confidence: 99%